The Relationship between Health Service Quality and Inpatient Revisit Interest - Yani, Fitri Amja; Agustina, Dewi; Gurning, Fitriani Pramita (Indonesian Journal of Global Health Research, 2024)
Interest in repeat visits is the response that arises when the patient wants to make a return visit. Assessment of the quality of health services aims to maintain the prevailing standards of service. The better the quality of services provided, the greater the chance of patients returning to visit. This study aims to determine the relationship between the quality of health services and the interest in revisiting inpatients at Rantauprapat Hospital. In this study, the type of research conducted was quantitative with a cross-sectional research design. The study was conducted at Rantauprapat Hospital, Labuhanbatu Regency in the inpatient room section in January-February 2024. The study population is all patients receiving treatment in the inpatient room of Rantauprapat Hospital as many as 17,070 patients in 2023 with a sample of 96 respondents using the Lemeshow formula. The sampling technique uses purposive sampling technique. The instrument used is a questionnair. Data analysis was performed by univariate and bivariate analysis. The results showed that there was a relationship between Reliability (p-value 0.015), Assurance (p-value 0.015), Tangible (p-value 0.015), Responsiveness (p-value 0.002) with Inpatient Revisit Interest at Rantauprapat Hospital, and there was no relationship between Emphaty (p-value 0.678) and Inpatient Revisit Interest at Rantauprapat Hospital. The conclusion is that reliability, responsiveness, tangible, assurance are significantly related while emphaty is not significantly related. Suggestions that the quality of doctor service quality still needs to be improved related to the schedule of doctor visits to patients and nurses are more informative to patients.